ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN KEPERCAYAAN DIRI SISWA MTs DI KABUPATEN BANDUNG BARAT - Rismayanti Nurpalah; Ninik Nuraeni Setyawidianingsih (Departement of Mathematics Education, 2019)
This study aims to analyze students' mathematical critical thinking skills and student confidence. The method used in this research is descriptive qualitative method. The sample studied was one class which amounted to 28 students in class IX A Mts Muslimin Citapen in the area of ​​West Bandung Regency. The instruments used are test and non-test questions. The test questions used were mathematical critical thinking test questions as many as 5 questions, and the non-test questions used were the questionnaire self confidence in each student. The results of the analysis obtained are the mathematical critical thinking skills of Mts in West Bandung Regency based on written description tests are still relatively low.